Fuel subsidies and income redistribution in Ecuador - H. Xavier Jara; Po Chun Lee; Lourdes Montesdeoca; Marcelo Varela (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper aims to evaluate the progressivity of different fuel subsidies in Ecuador as well as the budgetary and distributional effects of a potential elimination of such subsidies. Our analysis makes use of ECUAMOD, the tax-benefit microsimulation model for Ecuador, together with representative household microdata from ENIGHUR 2011-12. Our results show that domestic gas subsidy tends to be progressive, whereas gasoline and diesel subsidies tend to be regressive. Our simulations show that eliminating all fuel subsidies would increase poverty and inequality due to the importance of domestic gas subsidy for low-income households. Eliminating only gasoline and diesel subsidies would not impact poverty and inequality, while allowing to reduce government expenditure. We further show that using part of the budget saved from the elimination of fuel subsidies to increase social assistance payments in Ecuador, could be a mechanism to compensate low-income families for their loss following fuel subsidy elimination.
Keywords: D13; H24; I32; I38; 330; fuel subsidies; Ecuador; income distribution; microsimulation